Role of Vocational Education and Skill Training to Stimulate Human Development (Indian Journal of Social Science and Literature (IJSSL), 2024)
Vocational education and skill development work in tandem and are inextricably linked. In India, there is a need for vocational education that improves skill development because it is quite low in percentage when compared to traditional higher education. The study discusses the state of vocational education in the India. It also mentions the difficulties that vocational education faces, such as a lack of quality, obsolete modules, and insufficient courses. The report also looks at the government’s new policies and efforts aimed at improving the quality of vocational education and skill development in India. Finally, the key issues and opportunities for the sector’s future growth are emphasized from several systemic angles to stimulate human development.